Performing wellness, concealing pain: a gendered continuum of challenges for women with lupus in the workplace - Bam, Armand; Lulema, Joy (Frontiers in Psychology, 2025)
IntroductionWomen with systemic lupus erythematosus (SLE) work under conditions where success is often contingent on concealing pain, managing disclosure, and “performing” wellness in organisational cultures that reward composure over care. Workplaces are not neutral spaces; they are structured by ableist and gendered norms that privilege stability, productivity, and visibility, making episodic illness particularly disruptive.MethodsThis study draws on a narrative inquiry approach with eight professional women living with SLE. Participants were invited to recount their embodied experiences of illness, identity, credibility, and inclusion in the workplace. The narratives were analysed thematically with a feminist disability lens, attentive to the relational and institutional contexts that shape meaning-making.ResultsThe findings introduce the Continuum of Embodied Challenges, a conceptual framework tracing the layered tensions participants face in navigating illness and institutional expectations. Diagnosis emerges as both a clinical and epistemic struggle, where uncertainty erodes trust in one’s body. Participants described resisting the category of “disability” even when functionally impaired, and shouldering significant emotional and physical labour to remain credible in spaces that privilege predictability and presence.DiscussionBy centring invisibility, gender, and resistance, this study advances feminist disability perspectives on chronic illness and work. It highlights how episodic disablement is structurally misrecognised in organisations designed around uninterrupted performance. The study argues for institutional models of inclusion that account for bodily unpredictability, fluctuating capacity, and the complexity of living and working with episodic illness.